Effect of mold designs on molten metal behaviour in high-pressure die casting - Ibrahim, M.D; Rahman, M.R.; Khan, A.A; Mohamad, M.R; Suffian, M.S.Z.M.; Yunos, Y.S; Wong, L.K; Mohtar, M.Z (IOP Publishing Ltd., 2017)
This paper presents a research study conducted in a local automotive component manufacturer that produces aluminium alloy steering housing local and global markets. This study is to investigate the effect of design modification of mold in die casting as to improve the production rate. Design modification is carried out on the casting shot of the mold. Computer flow simulation was carried out to study the flow of molten metal in the mold with respect to the mold design modification. The design parameters of injection speed, die temperature and clamping force has been included in the study. The result of the simulation showed that modifications of casting shot give significant impact towards the molten flow behaviour in casting process. The capabilities and limitations of die casting process simulation to conduct defect analysis had been optimized. This research will enhance the efficiency of the mass production of the industry of die casting with the understanding of defect analysis, which lies on the modification of the mold design, a way early in its stages of production.